فعالية استخدام وسائط الصور في برنامج PowerPoint لترقية حفظ المفردات العربية لطلاب الفصل العاشر-ب في المدرسة العالية الإسلامية الأهلية "الحكم" جاتيريجو ديويك جومبانج - Ulya Hayin Amalyya; Mu’at Mu’at (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2023)
The use of image media in PowerPoint facilitates students' understanding and comprehension of the Arabic lesson, encouraging them to memorize Arabic vocabulary. Among these media, students can easily memorize Arabic vocabulary. The research questions are as follows: (1) How is Arabic vocabulary taught to tenth-grade students at the Islamic Private High School, Gatirijo Dewi Jombang? (2) How is PowerPoint's image media used for tenth-grade students at the Islamic Private High School, Gatirijo Dewi Jombang? (3) To what extent is the use of image media in PowerPoint effective in promoting Arabic vocabulary memorization for tenth-grade students at the Islamic Private High School, Gatirijo Dewi Jombang? This research employs quantitative research methods with an Ex Post De Facto type, where researchers do not have direct control over the independent variables because the phenomena are challenging to manipulate. The data collection methods used by the researcher include testing, questionnaires, and documentation. The research results show that the use of image media in PowerPoint has a positive effect on improving Arabic vocabulary memorization. The significance value (sig-2 tailed) is 0.000, which means that the value of 0.002 is less than 0.000. Therefore, we can conclude that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The R Square value (coefficient of determination) is 0.325, indicating that the use of image media in PowerPoint (x) on the variable of Arabic vocabulary memorization (y) is 0.325, approximately 32.5% or close to 33%. This research underscores the effectiveness of using PowerPoint to enhance Arabic language learning, especially in vocabulary memorization.